2022
DOI: 10.1039/d1en00752a
|View full text |Cite
|
Sign up to set email alerts
|

A nanocarrier pesticide delivery system with promising benefits in the case of dinotefuran: strikingly enhanced bioactivity and reduced pesticide residue

Abstract: There is a growing demand for reducing pesticide application to minimize its potential threats to food/environmental safety. Herein, a star polymer (SPc) with low production cost was synthesized using two...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 63 publications
(78 reference statements)
5
58
0
Order By: Relevance
“…As expected, the self-assembly of imidaclothiz/SPc complex could be easily realized through a simple mix and incubation at room temperature for 15 min. The imidaclothiz concentration was proportional to the ultraviolet absorption at 270 nm, and the PLC was calculated to be 16.31% ( Figure S1 ), which was a bit lower than those of dinotefuran (17.41%), osthole (17.09%) and thiamethoxam (20.63%) [ 16 , 17 , 18 ]. The loading efficiency of SPc is comparable to those of other polymer-based nanocarriers [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As expected, the self-assembly of imidaclothiz/SPc complex could be easily realized through a simple mix and incubation at room temperature for 15 min. The imidaclothiz concentration was proportional to the ultraviolet absorption at 270 nm, and the PLC was calculated to be 16.31% ( Figure S1 ), which was a bit lower than those of dinotefuran (17.41%), osthole (17.09%) and thiamethoxam (20.63%) [ 16 , 17 , 18 ]. The loading efficiency of SPc is comparable to those of other polymer-based nanocarriers [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The positive values of ΔH and ΔS demonstrated that the complexation of SPc with imidaclothiz was through hydrophobic association, revealing that the imidaclothiz was assembled in the hydrophobic core of SPc. Based on the current and our previous studies, the SPc can assemble with exogenous agents through different interactions [ 16 , 17 , 18 ], which is beneficial for expanding the application area of SPc.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations